A Utilization of Marketing Strategies Through to Increase Sales of Umkm Member Products of The Wijaya Cfd Association In Sampang Regency - Septian Eko Haryansyah; Zairina Zairina; Lailatul Hasanah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
UMKM Actors, the use of digital marketing is the most appropriate solution to survive amidst technological developments. Utilization in conducting marketing or online transactions, the approach in this digital era is all technology-based services. One of the emerging technologies is the increasing activity through social networks. This study uses a descriptive quantitative method design, where the results are obtained to obtain information data. The research plan carried out by the researcher aims to find out what promotions are used by the CFD association in Sampang Regency. How social media can increase sales of MSMEs in the CFD Association. The results of the study are: (a) the results of the correlation coefficient test on the Entrepreneurial Characteristics variable (X1) against Business Success (Y) of 0.646; (b) the results of the correlation coefficient test on the Entrepreneurial Competence variable (X2) against Business Success (Y) of 0.734; and (c) Based on the results of data processing in the study, it can be seen that the Adjusted R Square determination coefficient value is 0.627, meaning 62.7% of the success of MSMEs in the CFD Association of Wijaya Regency. Lacquer